The clinical basis of orthorexia nervosa: emerging perspectives - Koven NS (Dove Medical Press, 2015)
Nancy S Koven, Alexandra W Abry Department of Psychology, Bates College, Lewiston, ME, USA Abstract: Orthorexia nervosa describes a pathological obsession with proper nutrition that is characterized by a restrictive diet, ritualized patterns of eating, and rigid avoidance of foods believed to be unhealthy or impure. Although prompted by a desire to achieve optimum health, orthorexia may lead to nutritional deficiencies, medical complications, and poor quality of life. Despite its being a distinct behavioral pattern that is frequently observed by clinicians, orthorexia has received very little empirical attention and is not yet formally recognized as a psychiatric disorder. In this review, we synthesize existing research to identify what is known about the symptoms, prevalence, neuropsychological profile, and treatment of orthorexia. An examination of diagnostic boundaries reveals important points of symptom overlap between orthorexia and anorexia nervosa, obsessive–compulsive disorder (OCD), obsessive–compulsive personality disorder (OCPD), somatic symptom disorder, illness anxiety disorder, and psychotic spectrum disorders. Neuropsychological data suggest that orthorexic symptoms are independently associated with key facets of executive dysfunction for which some of these conditions already overlap. Discussion of cognitive weaknesses in set-shifting, external attention, and working memory highlights the value of continued research to identify intermediate, transdiagnostic endophenotypes for insight into the neuropathogenesis of orthorexia. An evaluation of current orthorexia measures indicates a need for further psychometric development to ensure that subsequent research has access to reliable and valid assessment tools. Optimized assessment will not only permit a clearer understanding of prevalence rates, psychosocial risk factors, and comorbid psychopathology but will also be needed to index intervention effectiveness. Though the field lacks data on therapeutic outcomes, current best practices suggest that orthorexia can successfully be treated with a combination of cognitive-behavioral therapy, psychoeducation, and medication. Keywords: orthorexia nervosa, diagnosis, psychometrics, neuropsychology, endophenotypes, treatment